'Doggy-biopolitics': Governing via the First Dog. (March 2017) - Skoglund, Annika; Redmalm, David
Biopolitics, traditionally understood as management of the human population, has been extended to include nonhuman animal life and posthuman life. In this article, we turn to literatures that advance Foucauldian biopolitics to explore the mode of government enabled by the dog of the US presidential family – the First Dog called Bo Obama. With analytical focus on vitalisation efforts, we follow the construction of Bo in various outlets, such as the websites of the White House and an animal rights organisation. Bo's microphysical escapades and the negotiation thereof show how contemporary biopolitics, which targets the vitality of the dog population, is linked to seductive neoliberal management techniques and subjectivities. We discuss 'cuddly management' in relation to Foucauldian scholarship within organisation and management studies and propose that the construction of Bo facilitates interspecies family norms and an empathic embrace of difference circumscribed by vitalisation efforts that we pinpoint as 'doggy-biopolitics'.